Craig's soil mechanics - Knappett, Jonathan; Craig, R. F. (Robert F.) (London ; New York : Spon Press, 2012)
""The reviewer considers that Dr Knappett, in revising this classic textbook, has made a substantial additional contribution to the years of service given by Dr Craig to the civil engineering profession, in general, and the geotechnical community in particular.""--Catherine O'Sullivan, Imperial College, London, UK""Jonathan Knappett is breathing a fresh lease of life into this old favourite with several new slants, including for the first time the design philosophy of Eurocode 7 and much new material ... I propose to keep it on our list of 'must consult' textbooks.""-Edward Bromhead, Kingston Uni.
Contents List of figures List of tables Preface Part 1: Development of a mechanical model for soil 1. Basic characteristics of soils Learning outcomes 1.1 The origin of soils 1.2 The nature of soils 1.3 Plasticity of fine-grained soils 1.4 Particle size analysis 1.5 Soil description and classification 1.6 Phase relationships 1.7 Soil compaction Summary Problems References Further reading 2. Seepage Learning outcomes 2.1 Soil water 2.2 Permeability and testing 2.3 Seepage theory 2.4 Flow nets 2.5 Anisotropic soil conditions 2.6 Non-homogeneous soil conditions 2.7 Numerical solution using the Finite Difference Method 2.8 Transfer condition 2.9 Seepage through embankment dams 2.10 Filter design Summary Problems References Further reading 3. Effective stress Learning outcomes 3.1 Introduction 3.2 The principle of effective stress 3.3 Numerical solution using the Finite Difference Method 3.4 Response of effective stress to a change in total stress 3.5 Effective stress in partially saturated soils 3.6 Influence of seepage on effective stress 3.7 Liquefaction Summary Problems References Further reading 4. Consolidation Learning outcomes 4.1 Introduction 4.2 The oedometer test 4.3 Consolidation settlement 4.4 Degree of consolidation 4.5 Terzaghi$1 (Bs theory of one-dimensional consolidations 4.6 Determination of coefficient of consolidation 4.7 Secondary compression 4.8 Numerical solution using the Finite Difference Method 4.9 Correction for construction period 4.10 Vertical drains 4.11 Pre-loading Summary Problems References Further reading 5. Soil behaviour in shear Learning outcomes 5.1 An introduction to continuum mechanics 5.2 Simple models of soil elasticity 5.3 Simple models of soil plasticity 5.4 Laboratory shear tests 5.5 Shear strength of coarse-grained soils 5.6 Shear strength of saturated fine-grained soils 5.7 The critical state framework 5.8 Residual strength 5.9 Estimating strength parameters from index tests Summary Problems References Further reading 6. Ground investigation Learning outcomes 6.1 Introduction 6.2 Methods of intrusive investigation 6.3 Sampling 6.4 Selection of laboratory test method(s) 6.5 Borehole logs 6.6 Cone Penetration Testing (CPT) 6.7 Geophysical methods 6.8 Contaminated ground Summary References Further reading 7. In-situ testing Learning outcomes 7.1 Introduction 7.2 Standard Penetration Test (SPT) 7.3 Field Vane Test (FVT) 7.4 Pressuremeter Test (PMT) 7.5 Cone Penetration Test (CPT) 7.6 Selection of in-situ test method(s) Summary Problems References Further reading Part 2: Applications in geotechnical engineering 8. Shallow foundations Learning outcomes 8.1 Introduction 8.2 Bearing capacity and limit analysis 8.3 Bearing capacity in undrained materials 8.4 Bearing capacity in drained materials 8.5 Stresses beneath shallow foundations 8.6 Settlements from elastic theory 8.7 Settlements from consolidation theory 8.8 Settlement from in-situ test data 8.9 Limit state design Summary Problems References Further reading 9. Deep foundations Learning outcomes 9.1 Introduction 9.2 Pile resistance under compressive loads 9.3 Pile resistance from in-situ test data 9.4 Settlement of piles 9.5 Piles under tensile loads 9.6 Load testing 9.7 Pile groups 9.8 Negative skin friction Summary Problems References Further reading 10. Advanced foundation topics Learning outcomes 10.1 Introduction 10.2 Foundation systems 10.3 Shallow foundations under combined loading 10.4 Deep foundations under combined loading Summary Problems References Further reading 11. Retaining structures Learning outcomes 11.1 Introduction 11.2 Limiting earth pressures from limit analysis 11.3 Earth pressure at rest 11.4 Gravity retaining structures 11.5 Coulomb$1 (Bs theory of earth pressures 11.6 Backfilling and compaction-induced earth pressures 11.7 Embedded walls 11.8 Ground anchorages 11.9 Braced excavations 11.10 Diaphragm walls 11.11 Reinforced soil Summary Problems References Further reading 12. Stability of self-supporting soil masses Learning outcomes 12.1 Introduction 12.2 Vertical cuttings and trenches 12.3 Slopes 12.4 Embankment dams 12.5 An introduction to tunnels Summary Problems References Further reading 13. Illustrative cases Learning outcomes 13.1 Introduction 13.2 Selection of characteristic values 13.3 Field instrumentation 13.4 The observational method 13.5 Illustrative cases Summary References Further reading Principal symbols Glossary Index
Previous edition under : Soil mechanics/ R.F. Craig.
Includes bibliographical references and index.
Keywords: Soil mechanics